Inovasi Pendidikan Karakter dalam Kurikulum 2013 dan Kurikulum Merdeka - Irawan, Hendri; Masyitoh, Iim Siti; Rahmat, Rahmat; Darmawan, Cecep; Anggraeni, Leni; Pradanna, Satrio Alpen (Universitas Indraprasta PGRI Jakarta, 2024)
Facing increasing complex challenges in an ever-evolving society, strengthening character education is considered an important aspect in shaping individuals who have integrity, ethics and good personality. The purpose of this study is to evaluate the various innovations in character education strengthening program models that have been implemented in the Indonesian curriculum from 2013 to 2022. This research used a descriptive qualitative approach with a literature study method to gather information from various reliable sources such as scientific journals, books and official publications. The main findings include the variety of innovative models that have been implemented, with positive impacts in shaping students' personalities, such as increased positive attitudes, social care, morality and integrity. However, challenges include a lack of understanding and full engagement from all parties involved in education. The conclusion of this study confirms that the integration of character education should be an integral part of the curriculum at all levels of education. This research makes an important contribution to the development of character education in Indonesia by introducing an innovative model to strengthen character education that has been implemented, while highlighting the challenges that still need to overcome.